MENINGKATKAN HASIL BELAJAR SISWA KELAS XI TATA BUSANA SMK NEGERI 3 KOTA BOGOR MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING MATERI DESAIN ROK SESUAI KONSEP KOLASE - Siti Syarifah Hidayanti (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
IMPROVING STUDENT LEARNING OUTCOMES IN CLASS 11 FASHION DESIGN FOR VOCATIONAL HIGH SCHOOLS (SMK NEGERI 3 KOTA BOGOR) THROUGH A PROJECT BASED LEARNING MODEL ON SKIRT DESIGN ACCORDING TO THE COLLAGE CONCEPTThe purpose of this study was to determine the increase in student learning outcomes regarding Skirt Design material according to the Collage Concept of the Fashion Design subject in class 11 Fashion Design-2 Vocational High Schools through the use of the Project Based Learning Model. The research subjects were students in class 11 Fashion Design-2 consisting of 34 female students. The method used is a class action research method consisting of two cycles. In the first cycle, learning is carried out using the Project Based Learning Model, while in the second cycle, it uses an enhanced Project Based Learning Model. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of the Project Based Learning Learning Model can improve student learning outcomes about Skirt Design material according to the Collage Concept in the Fashion Design subject in class XI Dressmaking-2 Vocational High School. It is proven that the percentage of student learning outcomes has increased from the initial condition the average value of daily tests was 66.18 in cycle I to 75.21 and in cycle II to 81.32 or in the final condition there was an increase of 22.88% from the initial condition. It is proven that the percentage of students' learning completeness increased from the initial conditions of 73.53% in cycle I and to 91.18% in cycle II or in the final conditions an increase of 24.00% from the initial conditions.